Analyzing End Effect of Single-Sided LIM by Using Wavelet Filter Bank - (:unkn) unknown (DRUNPP-SARAJEVO, 2011)
The linear induction motor (LIM) applications have been increasing with developing technology day by day. In order to increase system performance and efficiency, LIM applications have been preferred. Concurrently, researchers have focused on LIM. In this study, end effect of single-sided LIM is analyzed. Firstly, non-sinusoidal magnetic flux of the secondary surface was measured by measurement coils placed in the secondary block. After placing end coils at entry and exit side of primary, magnetic flux values were remeasured. Measured magnetic flux values decomposed two components (end effect and main signals) by means of discrete wavelet transform in operating with end coils and without end coils. The second level decomposition of measured magnetic values was carried out by Simulink wavelet filter bank and then approximation and details coefficients of magnetic flux were obtained. To get end effect signal, details coefficients and to get main signal, approximation coefficient were synthesized respectively. It was observed that placed end coils reduced entry and exit end effects.
Keywords: LINEAR INDUCTION-MOTOR